2013
DOI: 10.1016/j.molcel.2013.01.035
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-Dependent Degradation of TXNIP upon Energy Stress Leads to Enhanced Glucose Uptake via GLUT1

Abstract: Summary TXNIP is an α-arrestin family protein that is induced in response to glucose elevation. It has been shown to provide a negative feedback loop to regulate glucose uptake into cells, though the biochemical mechanism of action has been obscure. Here, we report that TXNIP suppresses glucose uptake directly by binding to the glucose transporter, Glut1, inducing Glut1 internalization through clathrin coated pits, as well as indirectly by reducing the level of Glut1 mRNA. In addition, we show that energy stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
565
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 564 publications
(592 citation statements)
references
References 51 publications
22
565
2
3
Order By: Relevance
“…Glucose availability affects ROS production in cells, and high glucose uptake induces cellular senescence (Mortuza et al, 2013). Previous reports have revealed that TXNIP regulates glucose uptake in peripheral tissues in both an insulin‐dependent and insulin‐independent manner and suppresses glucose uptake by regulating the expression and internalization of GLUT1 (Parikh et al, 2007; Wu et al, 2013). From these previous reports, we hypothesized that TXNIP might regulate cellular senescence by regulating the balance of glucose uptake and ROS production.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Glucose availability affects ROS production in cells, and high glucose uptake induces cellular senescence (Mortuza et al, 2013). Previous reports have revealed that TXNIP regulates glucose uptake in peripheral tissues in both an insulin‐dependent and insulin‐independent manner and suppresses glucose uptake by regulating the expression and internalization of GLUT1 (Parikh et al, 2007; Wu et al, 2013). From these previous reports, we hypothesized that TXNIP might regulate cellular senescence by regulating the balance of glucose uptake and ROS production.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we examined the induction of glucose uptake in KO MEF cells (Figure 1i) and KO mice (Figure 4a,b, 5a, and Supporting Information Figure S4D). Although previous reports have revealed the role of TXNIP in the regulatory mechanisms of glucose uptake and glucose metabolism in cancer and primary cells, the function of TXNIP in cellular senescence under glucose stress has not been reported (DeBalsi et al, 2014; Hui et al, 2008; Wu et al, 2013). High glucose is a well‐known inducer of cellular ROS and accelerates the senescence of cells (Mortuza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding site of HIF-1-alpha, namely the hypoxia response element (HRE), is present in the human and rat GLUT1 promoter regions (Behrooz and Ismail-Beigi 1997;Zelzer et al 1998). Recently, Wu et al (2013) reported that knockdown of thioredoxin interacting protein (TXNIP) expression increased GLUT1 expression in HepG2 hepatocellular carcinoma cells, but the details of the regulatory mechanism are unknown. TXNIP was originally cloned as a 1α,25-dihydroxy vitamin D 3 -inducible protein in HL-60 cells (Chen and DeLuca 1994).…”
Section: Introductionmentioning
confidence: 99%